The Emergence of an “Intersecting Circle” in Kachru’s Three Concentric Circles of World Englishes: A Case of Ethno-linguistic Neutrality in Central Nigeria - Okpeh, Peter Ochefu; Udaa, James (Lingual Journal of Language and Culture, 2021)
There is evidence that contemporary Nigeria is drifting towards a society of monolingual English users a component of which could be defined as lacking in ethno-linguistic identity. This trend is found among a generation of young Nigerian urban dwellers (between the age bracket of (12 and 25) who can neither communicate in their parents’ native language(s) nor indeed in any other Nigerian indigenous language; their only medium of communication is English. Although based on their childhood exposure to the English language and their relative competence in it, English can be described as their ‘‘mother tongue’’ but the fact that they are not native speakers given the socio-geographical circumstances of their birth excludes them from Kachru’s (1988) Inner Circle classification of native speakers. Consequently, these Nigerians are left without a clearly defined ethno-linguistic affiliation. This paper interrogates this emerging sociolinguistic phenomenon in especially Central Nigeria, with the aim of stimulating scholarly consciousness on the ethno-linguistic identity of this category of Nigerians, and its implications for English usage among them. The submission of the paper is that another circle, “the intersecting circle”, be created for them since they bestride both the inner circle in having English as their “mother tongue” and yet they are not native speakers of the language